Stratigraphy and paleontology (plant and arthropod fossils) from the Late Neogene Niguanak site, Arctic Slope, Northern Alaska - L. David Carter; Donna Christensen; David M. Hopkins; John V. Matthews; Robert E. Nelson; Lynn E. Ovenden; Natalia Rybczynski; Tamara L. Fletcher (Arctic, Antarctic, and Alpine Research)
Motivated by the need for more paleodata for Pliocene paleoclimate data-model comparison, we revisited unpublished investigations of a fossiliferous site on the Niguanak River in Arctic North America. Analyses of the samples indicates forested conditions during an early phase of sedimentation in which environments were perhaps similar to those near tree line in the modern Anchorage area or farther south along the Pacific coast, whereas during a later phase of sedimentation, environments were characterized by shrub tundra vegetation and were possibly similar to the present-day conditions in the interior of southern Seward Peninsula. We describe the site stratigraphy and discuss the macrofossils and pollen recovered from the sediments, their paleoecological implications, and their significance for paleoclimate and sea ice. Mean annual temperatures were found to be 12.7°C warmer than current, with a pattern of much warmer winters, and less difference in summer warming as observed at other Pliocene Arctic sites. Finally, we discuss possible age assignments for the sediments, based on regional stratigraphy and geomorphology, and the probable sequence of evolution of arctic borderland climate and ecosystems.